The IMPROVEMENT OF SCIENTIFIC WRITING SKILLS USING THE PROJECT-BASED LEARNING MODEL (PjBL) ON STUDENTS OF CLASS XI.4 SMA NEGERI 3 PALEMBANG: PENINGKATAN KETERAMPILAN MENULIS KARYA ILMIAH MENGGUNAKAN MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) PADA SISWA KELAS XI.4 SMA NEGERI 3 PALEMBANG - Rizki Mardatilla, Awalia; Karmila, Emi; Fitriani, Yessi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
This study was conducted on the condition that the students scientific writing skills were low. The purpose of this study was to improve the scientific writing skills of students in class XI.4 using the Project Based Learning (PjBL) learning model. This research is a classroom action research conducted in two cycles referring to the Kemmis and Mc Taggart model including: planning, action, observation and reflection. Based on the research that has been carried out, it is concluded that the project-based learning (PjBL) learning model can improve scientific writing skills in class XI.4 SMA Negeri 3 Palembang students. This is proven by the results of observations and tests carried out on students of class XI.4 in Indonesian language learning with scientific writing material there is an increase in the percentage of each cycle starting from pre-cycle, cycle 1, and cycle 2. At the pre-cycle stage, the results obtained by the students' average score were 67.73 with a percentage of students' score completeness of 40%. Then at the cycle 1 stage, the average result of the scientific writing skills of XI.4 class students was 71.47 with a percentage of completeness of 53.33%. At the cycle 2 stage, the average score of students was 82.53 with a percentage of completeness of 88.88%. From this explanation, it can be seen that cycle 2 can improve the scientific writing skills of students in class XI.4 SMA Negeri 3 Palembang with a better percentage of 88.88%.